-4x(2x-3)=7(x+8)

Simple and best practice solution for -4x(2x-3)=7(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x(2x-3)=7(x+8) equation:


Simplifying
-4x(2x + -3) = 7(x + 8)

Reorder the terms:
-4x(-3 + 2x) = 7(x + 8)
(-3 * -4x + 2x * -4x) = 7(x + 8)
(12x + -8x2) = 7(x + 8)

Reorder the terms:
12x + -8x2 = 7(8 + x)
12x + -8x2 = (8 * 7 + x * 7)
12x + -8x2 = (56 + 7x)

Solving
12x + -8x2 = 56 + 7x

Solving for variable 'x'.

Reorder the terms:
-56 + 12x + -7x + -8x2 = 56 + 7x + -56 + -7x

Combine like terms: 12x + -7x = 5x
-56 + 5x + -8x2 = 56 + 7x + -56 + -7x

Reorder the terms:
-56 + 5x + -8x2 = 56 + -56 + 7x + -7x

Combine like terms: 56 + -56 = 0
-56 + 5x + -8x2 = 0 + 7x + -7x
-56 + 5x + -8x2 = 7x + -7x

Combine like terms: 7x + -7x = 0
-56 + 5x + -8x2 = 0

Begin completing the square.  Divide all terms by
-8 the coefficient of the squared term: 

Divide each side by '-8'.
7 + -0.625x + x2 = 0

Move the constant term to the right:

Add '-7' to each side of the equation.
7 + -0.625x + -7 + x2 = 0 + -7

Reorder the terms:
7 + -7 + -0.625x + x2 = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -0.625x + x2 = 0 + -7
-0.625x + x2 = 0 + -7

Combine like terms: 0 + -7 = -7
-0.625x + x2 = -7

The x term is -0.625x.  Take half its coefficient (-0.3125).
Square it (0.09765625) and add it to both sides.

Add '0.09765625' to each side of the equation.
-0.625x + 0.09765625 + x2 = -7 + 0.09765625

Reorder the terms:
0.09765625 + -0.625x + x2 = -7 + 0.09765625

Combine like terms: -7 + 0.09765625 = -6.90234375
0.09765625 + -0.625x + x2 = -6.90234375

Factor a perfect square on the left side:
(x + -0.3125)(x + -0.3125) = -6.90234375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 3x-2x+40=24 | | X^2+8x+19=4 | | 2(-5+3m+2)= | | 1/2(6x+2)=29 | | 27-3x=6 | | 6d=2(d-4) | | 7n^5(8n^2-8n+4)= | | (x+40)=(6x+20) | | 19m=20+19m | | 20x+.15=30x+.10 | | x+(x*.0635)=20 | | 3/3x-21 | | y=-.5x(x)-2x-3 | | 5x-10=-4x-8 | | -6(-2x-1/2)=123 | | 0+32x=25+30x | | 13+2=-3(6x-5) | | -6p-3=-9 | | 26x+4x=30x*35+30x | | x-3=4+2(x+5) | | 5(2x+3)=96 | | 148=5+2(5+3)+45-5 | | 3e^8x=9 | | (v-5)(5v-7)= | | 6/2x-7 | | 2(2y+3)+2=4y+5 | | 2x+4(2x-8)+2= | | 3cos(x)=1+cos(x) | | 7x+3x+1+25=76 | | 5(1+7x)=320 | | (2x+3)*(1+x)=4x^2-22 | | 2/3z=4/1/4 |

Equations solver categories